Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Nasabah Yang Berdampak Pada Loyalitas Nasabah Pada Bank Permata Bintaro Tower III - Sela Novitasari; Anisa Rahmawati (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to analyze and prove "The Effect of Service Quality and Promotion on Customer Satisfaction Which Has An Impact On Customer Loyalty At Bank Permata Bintaro Tower III". The research method used in this study was by determining accidental sampling of 160 respondents, and the data analysis methods used were validity test, reliability test, classical assumption test, regression test, determination coefficient test, hypothesis test, path analysis, sobel test. Based on the results of the study, the following findings were obtained: the quality of service has a positive and significant effect on customer satisfaction at Bank Permata Bintaro Tower III. This can be shown by a t-count value of 40.788 and a significance value of 0.000. The promotion has proven to have a positive and significant effect on customer satisfaction at Bank Permata Bintaro Tower III. This can be shown a t-count value of 12.621 and a significance value of 0.000. The quality of service and promotion has proven to have a positive and significant effect on customer satisfaction at Bank Permata Bintaro Tower III. This can be shown an f-count value of 861.441 and a significance value of 0.000. The quality of service has proven to have a positive and significant effect on customer loyalty at Bank Permata Bintaro Tower III. This can be shown a t-count value of 19.272 and a significance value of 0.000. The promotion has proven to have a positive and significant effect on customer loyalty at Bank Permata Bintaro Tower III. This can be shown a t-count value of 12.111 and a significance value of 0.000. Customer satisfaction has proven to have a positive and significant effect on customer loyalty at Bank Permata Bintaro Tower III.